Optimum design of hybrid renewable energy systems: Overview of different approaches - Erdinc, O.; Uzunoglu, M. (PERGAMON-ELSEVIER SCIENCE LTD, 2012)
Public awareness of the need to reduce global warming and the significant increase in the prices of conventional energy sources have encouraged many countries to provide new energy policies that promote the renewable energy applications. Such renewable energy sources like wind, solar, hydro based energies, etc. are environment friendly and have potential to be more widely used. Combining these renewable energy sources with back-up units to form a hybrid system can provide a more economic, environment friendly and reliable supply of electricity in all load demand conditions compared to single-use of such systems. One of the most important issues in this type of hybrid system is to optimally size the hybrid system components as sufficient enough to meet all load requirements with possible minimum investment and operating costs. There are many studies about the optimization and sizing of hybrid renewable energy systems since the recent popular utilization of renewable energy sources. In this concept, this paper provides a detailed analysis of such optimum sizing approaches in the literature that can make significant contributions to wider renewable energy penetration by enhancing the system applicability in terms of economy. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Hybrid system; Optimization; Renewable energy; Sizing; WIND POWER-GENERATION; ARTIFICIAL IMMUNE-SYSTEM; PARTICLE SWARM OPTIMIZATION; ANT COLONY OPTIMIZATION; FUZZY-LOGIC CONTROL; TECHNOECONOMIC ANALYSIS; PHOTOVOLTAIC SYSTEM; GENETIC ALGORITHMS; RURAL ELECTRIFICATION; FEASIBILITY ANALYSIS; Science & Technology - Other Topics; Energy & Fuels